Sensing nanoparticle-protein corona using nanoparticle enhanced Laser Induced Breakdown Spectroscopy signal enhancement - Dell'Aglio, Marcella; Salajková, Zita; Mallardi, Antonia; Sportelli, Maria Chiara; Kaiser, Jozef; Cioffi, Nicola; De Giacomo, Alessandro (Talanta, 2021)
Recently nanoparticle enhanced Laser Induced Breakdown Spectroscopy (NELIBS) is getting a growing interest as an effective alternative method for improving the analytical performance of LIBS. On the other hand, the plasmonic effect during laser ablation can be used for a different task rather than elemental analysis. In this paper, the dependence of NELIBS emission signal enhancement on nanoparticle-protein solutions dried on a reference substrate (metallic titanium) was investigated. Two proteins were studied: Human Serum Albumin (HSA) and Cytochrome C (CytC). Both proteins have a strong affinity for the gold nanoparticles (AuNPs) due to the bonding between the single free exterior thiol (associated with a cysteine residue) and the gold surface to form a stable protein corona. Then, since the protein sizes are vastly different, a different number of protein units is needed to cover AuNP surface to form a protein layer. The NP-protein solution was dropped and dried onto the titanium substrate. Then the NELIBS signal enhancement of Ti emission lines was correlated to the solution characteristics as determined with Dynamic Light Scattering (DLS), Surface Plasmon Resonance (SPR) spectroscopy and Laser Doppler Electrophoresis (LDE) for ζ-potential determination. Moreover, the dried solutions were studied with TEM (Transmission Electron Microscopy) for the inspection of the inter-particle distance. The structural effect of the NP-protein conjugates on the NELIBS signal reveals that NELIBS can be used to determine the number of protein units required to form the nanoparticle-protein corona with good accuracy. Although the investigated NP-protein systems are simple cases in biological applications, this work demonstrates, for the first time, a different use of NELIBS that is beyond elemental analysis and it opens the way for sensing the nanoparticle protein corona.
Keywords: Spectrum Analysis; lasery; kovové nanočástice; Humans; Gold; Metal Nanoparticles; lidé; zlato; Lasers; Protein Corona; proteinová korona; spektrální analýza